2019
DOI: 10.1111/ssm.12318
|View full text |Cite
|
Sign up to set email alerts
|

The impact of integrated STEM professional development on teacher quality

Abstract: This study of a state‐funded, 3‐year implementation of an integrated STEM professional development (PD) program for teachers from two middle schools in the midwestern U.S. examined if participants in the PD were enabled to transform their practice and perceptions of STEM. An integrated STEM approach includes a focus on the STEM disciplines, along with leveraging social studies/history and English/language arts as important context and tools for solving society’s biggest challenges. Findings in this study indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 24 publications
1
27
0
2
Order By: Relevance
“…Teachers need support in STEM teaching and learning with the integration of STEM disciplines and appropriate resources for such pedagogical approaches (Estapa & Tank, 2017). Professional development should provide support to teachers' dynamics in shifting to innovative pedagogical practices and integrating the different disciplines effectively (Du et al, 2019). Professional development for teachers can often successfully support self-efficacy and reduce challenges associated with STEM practices (Seals, Mehta, Berzina-Pitcher, & Graves-Wolf, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Teachers need support in STEM teaching and learning with the integration of STEM disciplines and appropriate resources for such pedagogical approaches (Estapa & Tank, 2017). Professional development should provide support to teachers' dynamics in shifting to innovative pedagogical practices and integrating the different disciplines effectively (Du et al, 2019). Professional development for teachers can often successfully support self-efficacy and reduce challenges associated with STEM practices (Seals, Mehta, Berzina-Pitcher, & Graves-Wolf, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Du et al. (2019) investigated how an integrated STEM PD transformed 50 teachers’ practices and perceptions of STEM. They found that the PD helped the teachers implement more effective STEM practices, increased the teachers’ positive perceptions of STEM, and made the teachers aware of the support they needed to implement STEM.…”
Section: Review Of Relevant Literaturementioning
confidence: 99%
“…Mathematics education research indicates teachers need opportunities to learn and connect STEM content, as they often do not receive such training in teacher preparation programs (Guzey, Moore, & Harwell, ; Honey et al, ). Professional development focusing on STEM integration can be a successful way to support teacher STEM knowledge and integration (Du et al, ). However, teacher attributes can impact the effectiveness of the professional development and should be considered when designing and evaluating teacher interventions (Huffman, Thomas, & Lawrenz, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This approach is beneficial, as the integrating science and mathematical concepts can support understanding better than teaching concepts in an isolated discipline (Czerniak & Johnson, ). For teachers to capitalize on these opportunities, they must understand and support content integration for their students (Du et al, ).…”
Section: Introductionmentioning
confidence: 99%